PENGARUH OPINI AUDITOR, PERGANTIAN AUDITOR DAN REPUTASI AUDITOR TERHADAP AUDIT DELAY DAN DAMPAKNYA TERHADAP BIAYA MODAL PERUSAHAAN - Zumratul Meini; Roikhana Umiyatun Nikmah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of auditor opinion, auditor turnover, and auditor reputation on audit delay and its impact on the cost of equity capital. The sample used in this study were 73 manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2019. The results of this study indicate that auditor's opinion and auditor's reputation have a negative effect on audit delay, thus auditor's opinion and auditor's reputation are proven to be important factors that can cause companies to experience audit delay. Then, audit delay has a negative effect on the cost of equity capital, a long audit delay does not indicate the company's performance and the auditor's performance is not good, so it does not get a negative assessment from investors as indicated by the imposition of a low cost of capital. Furthermore, auditor reputation has a positive effect on the cost of equity capital. The imposition of a low cost of capital for companies audited by non-bigfour auditors also shows that investors actually view that they are more careful and professional in carrying out audit work.